Pseudoxanthoma Elasticum: An Interesting Model to Evaluate Chronic Kidney Disease-Like Vascular Damage without Renal Disease (2020)
Background: Pseudoxanthoma elasticum (PXE; OMIM 264800) is an inherited multisystem disorder associated with accumulation of mineralized and fragmented elastic fibers in the skin, vascular walls, and brush membrane in the eye. Carriers exhibit characteristic lesions in the cardiovascular system, and peripheral and coronary arterial disease as well as mitral valvulopathy often present as a cardiovascular feature of this disease. PXE and chronic kidney disease (CKD) share some common patterns in the vascular damage and in therapeutic approaches as well. Summary: To date, treating PXE has focused more on careful follow-up examinations with retinal specialists and cardiologist, avoiding long-term anticoagulation. Like CKD, maintaining a low-calcium diet, increasing dietary magnesium, and administering phosphate binders such as aluminum hydroxide or sevelamer may yield a modest benefit. Recently, 4-phenylbutyrate acid (4-PBA) has demonstrated a maturation of ABCC6 mutant effects into the plasma membrane. Moreover, in a humanized mouse model of PXE, 4-PBA administration restored the physiological function of ABCC6 mutants, resulting in enhanced calcification inhibition and thus a promising strategy for allele-specific therapy of ABCC6-associated calcification disorders. Key Message: Vascular compromise in PXE patients share some components similar to CKD.